Entrectinib use in a platinum-refractory mucinous ovarian cancer harboring a NTRK3 gene fusion - Olivia G. Beck; Melissa M. Hardesty (Elsevier, 2023)
Ovarian cancer is difficult to treat, and the mucinous epithelial subtype has a particularly poor response to traditional chemotherapy regimens. Entrectinib is a tumor-agnostic tyrosine kinase inhibitor with limited data regarding its use in ovarian cancers, though it demonstrates significant tumor response and patient tolerability in other settings. Here we outline what we believe to be the first case in which Entrectinib was successfully utilized to treat a patient with mucinous ovarian cancer. A 51-year-old woman with stage IVB mucinous ovarian cancer possessing a KANK1-NTRK3 gene fusion experienced tumor progression and clinical deterioration with conventional chemotherapeutics. Upon initiation of Entrectinib treatment she experienced rapid clinical improvement, with significant partial response and sustained decrease in tumor markers.